Extensive plastid-nuclear discordance in a recent radiation of Nicotiana section Suaveolentes (Solanaceae). (24th May 2020) - Dodsworth, Steven; Christenhusz, Maarten J M; Conran, John G; Guignard, Maïté S; Knapp, Sandra; Struebig, Monika; Leitch, Andrew R; Chase, Mark W
Abstract: Nicotiana section Suaveolentes is the largest section of Nicotiana and is a monophyletic group of allotetraploid species. Most of the species are endemic to Australia, but three species occur on islands in the South Pacific as far east as French Polynesia and one species is native to Namibia. Here, we present phylogenetic results based on genome skimming, with near-complete taxon sampling and multiple accessions sampled for several species. These represent the first phylogenetic results for the section that include most recognized taxa, using wild-sourced material wherever possible. Despite known chromosome number and genome size changes in the section, there is little divergence in the ribosomal DNA operon (26S, 18.S and 5.8S plus associated spacers) and plastid genomes, with little to no taxonomic signal in plastome phylogenetic results and clear plastid-nuclear discordance. These results contrast with strong morphological differentiation (both floral and vegetative) between most of the core Australian taxa and obvious differences in ecological preferences. Together, these initial results portray Nicotiana section Suaveolentes as experiencing recent and ongoing radiation in the arid zone of Australia.